Шляхи і напрями удосконалення законодавства про вибори народних депутатів України: теоретико-методологічні та законодавчі аспекти (частина 1) - Федоренко, В.; Малюга, А.; Fedorenko, V.; Malyuga, А. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
Публікація присвячена дослідженню проблем оновлення чинного законодавства про вибори народних депутатів України у 2014 році. Вивчаються аксіологічні аспекти виборів як основоположної форми прямого народовладдя. Досліджуються традиційні і нові підходи до визначення сутності та змісту виборів, виборчих систем і виборчого процесу та його окремих процедур.Аналізуються та систематизуються законодавчі ініціативи, спрямовані на удосконалення чинного Закону України «Про вибори народних депутатів України», що подавались на розгляд Верховної Ради України у червні-серпні 2014 року. Виокремлюються законодавчі новації, які мають бути враховані новообраним парламентом при оновленні чинного виборчого законодавства України. The main idea of the article is devoted to the study of problems updating the existing legislation on elections of deputies of Ukraine in 2014. The axiological aspects of elections have been explored as a core form of the direct democracy. The traditional and new approaches to the study of the nature and content of elections have been explored with their electoral systems and electoral process and individual procedures. The legislative initiatives have been analyzed and organized. They were aimed at improving the current Law of Ukraine «About the Election of Deputies of Ukraine» which were submitted to the Verkhovna Rada of Ukraine in June-August 2014. The legislative novations have been appropriated that can be taken into account by new parliament during the updating of the election legislation of Ukraine.
Ways and Directions of Improving the Legislation of Deputies’ Elections: Theoretical, Methodological and Legislative Aspects (Part 1)
Keywords: вибори; виборча система; виборчий процес; виборче законодавство; вибори народних депутатів України; the elections; election system; election process; the electoral laws; he election of people's deputies of Ukraine